Collagen fibers in human prostatic lesions: histochemistry and anisotropies - Taboga, S. R. [UNESP]; De Campos Vidal, B. (My University, 2003)
The present study focuses on establishing patterns of collagen fibers distribution in prostatic nodular hyperplasia and adenocarcinomas, in comparison with the normal tissue. Sections of prostatic transurethral resection were subjected to Gömöri's method for collagen fibers and reticulin and analyzed under ordinary and polarized light microscopy. Controls and hyperplastic regions present collagen fibers with variable thickness that run in different directions, establishing a tridimensional network. These fibers exhibit birefringence and dichroism thus demonstrating their fibrillar integrity. On the other hand, increased variability in collagen fiber distribution and anisotropical properties occur in adenocarcinomas evaluated in accordance with the Gleason's score. In some of their areas, a well-defined collagen network delimitates the base of transformed epithelial cells whereas in other areas the collagen fibers are disorganized and do not establish a boundary between the epithelial structures and the stroma. In these areas, collagen is found in the stroma. It was also observed that adenocarcinoma tumor cells rest on a scaffold of thin and dendritic collagen fibers. Collagen fibers of the prostatic stroma of the adenocarcinomas may show a modification in arrangement and fibrillar compactness. In prostatic nodular hyperplasia, there is no change in collagen molecular integrity, since collagen affinity for silver and collagen birefringence are similar to controls. In adenocarcinoma with high dedifferentiation degree, thin and branched strongly argyrophilic and birefringent collagen fibers are detected in regions of cell proliferation. In the adjacent stroma, hyaline plaques are indicative of matrix degradation or remodellation.
Keywords: Argentic impregnation; Collagen fibers; Polarization microscopy; Prostate; collagen fiber; hyalin; reticulin; silver; analytic method; anisotropy; binding affinity; cell differentiation; cell proliferation; controlled study; epithelium; evaluation; histochemistry; human; human cell; microscopy; nodular hyperplasia; prostate adenocarcinoma; prostate carcinoma; prostate hypertrophy; protein degradation; protein folding; protein localization; protein modification; protein structure; stroma cell; transurethral resection